Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Produk Wardah (Studi Kasus pada Mahasiswa FISIPOL Universitas Muhammadiyah Mataram) - Andini, Dwi Tesna (Al-DYAS, 2023)
This study aims to determine the effect of brand image and product quality on purchasing decisions for Wardah products. This study uses two independent variables, which brand image and product quality and one dependent variable, which purchasing decisions. The data in this study were collected by distributing questionnaires to 102 students of Faculty of Social and Political Sciences at Muhammadiyah University of Mataram who used Wardah products as research samples. The sampling technique used was purposive sampling and the data analysis method used quantitative. Based on data analysis, the research results show that the indicators in this study are valid and reliable. In the R test it is known that the magnitude of the influence of brand image and product quality on purchasing decisions is 65.3%. While the remaining 34.7% is influenced by other factors outside of brand image and product quality variables.